Victims of Ireland's great famine : the bioarchaeology of mass burials at Kilkenny Union Workhouse - Geber, Jonny (Bioarchaeological interpretations of the human past: local, regional, and global perspectives, 2016)
The Great Famine (1845-1852) is a watershed in Irish history. With one million dead and just as many forced to flee hunger, starvation, and disease, Irelands 'Great Hunger' is among the worst famines in human history. In 2006, a mass burial ground containing the skeletal remains of near 1,000 of its victims was found on the grounds of the former Kilkenny Union Workhouse. This book presents bioarchaeological analysis of these findings along with historical research on the burial ground and the people buried within it.